Review of the jumping tree bugs (Hemiptera: Heteroptera: Miridae: Isometopinae) of Argentina and nearby areas of Brazil and Paraguay, with descriptions of nine new species - Henry, Thomas J. (2012)
Nine new species of jumping tree bugs, or Isometopinae, from Argentina, Paraguay, and southern Brazil are described. The genus Aristotelesia is revised and the two new species A. fuscata (from Brazil) and A. medialis (from Argentina) are described, and the Argentine and Paraguayan species of Myiomma are reviewed and the seven new species M. apicalis (from Paraguay), M. argentinensis (from Argentina and Paraguay), M. binotata (from Argentina), M. pallidopleura (from Argentina), M. pallipes (from Argentina), M. scutellata (from Paraguay), and M. uniformis (from Argentina) are described. Previously published records of isometopines from Argentina are clarified. Color photographs, illustrations of the parameres of M. argentinensis, and keys are provided to help distinguish species.